P01.136 Safety and adverse event profile of tumor treating fields in elderly patients - a post-market surveillance analysis. (19th September 2018) - Glas, M; Kebir, S; Shi, W
Abstract: Background: Tumor Treating Fields (TTFields) are an established modality for glioblastoma (GBM) treatment administered through the portable Optune system. The efficacy of Optune in newly diagnosed GBM was previously demonstrated in the EF-14 phase 3 trial (n=695). Optune plus temozolomide significantly improved survival in all patient subgroups compared to temozolomide alone, which included those patients ≥ 65 years of age (median OS: 17.1 vs 13.7 months). Here, we report post-marketing surveillance data from elderly patients treated with Optune. Material and Methods: A review of adverse events in patients≥65 years of age. Post-market surveillance data were analyzed based on the MedDRA body system (system organ class) preferred terms. Results: A total of 8025 patients were treated with Optune (newly diagnosed glioblastoma 46.1%, recurrent glioblastoma 46.2%, other 7.7%). Of those 2574 patients (32.1%) were ≥ 65 years of age at the time of Optune treatment. 46% of these elderly patients reported ≥ 1 adverse event. Skin reaction was the most prevalent adverse event and occurred in 28% of patients. Similarly, 47% of patients ≥ 18 and <65 years of age (N=5421) experienced at least 1 adverse event and 27% developed skin reaction. The remaining adverse events profile was fairly equally distributed between both age groups. Conclusion: This retrospective analysis demonstrates that Optune is used in patients 65 years of age or older. The adverse event profile in this group of elderly patients is comparable to patients younger than 65 years. The most common adverse event registered was skin reaction, which was also found in the phase 3 EF-11 trial for recurrent GBM and in the EF-14 trial for newly diagnosed GBM patients. In summary, these results underline the safety profile of Optune.